Invasive behaviour of oak lace bug in forest ecosystems: a comparative analysis between thermophilous and mesophilous oak forests - Bălăcenoiu, Flavius; Nețoiu, Constantin; Toma, Dragoș; Petrițan, Ion Cătălin (Frontiers in Forests and Global Change, 2024)
Forest ecosystems provide invaluable ecological, economic, and social benefits, making them essential for global well-being. However, these ecosystems face various threats, including biological invasions by alien species. Among these, the oak lace bug (OLB), an invasive North American insect, has rapidly spread in Europe, impacting oak forests and raising concerns about its adaptation to new environments. OLB feeds on the undersides of oak leaves, extracting sap and causing chlorotic discoloration. Severe infestations lead to premature defoliation, increased susceptibility to diseases or pests and can also result in a substantial reduction in photosynthesis activity. This study aims to analyse OLB’s invasive behaviour in Romanian forest ecosystems, with a specific focus on the differences between thermophilous and mesophilous oak forests. The analysis covers 6 years of data and reveals critical insights. In the initial 4 years, OLB predominantly inhabited the extracarpathian regions of Romania, with concentrated presence in the southern, western, and northwestern areas. Forest ecosystems mainly affected between 2017 and 2020 were characterized by thermophilous oak forests in southern and western regions. However, in the last 2 years (2021–2022), OLB presence increased, particularly in lowland ecosystems, albeit with reduced damage intensity. The analysis also unveiled an adaptation and expansion of OLB in mesophilous forest ecosystems. Climatic factors, specifically temperature and precipitation, significantly influenced OLB’s behaviour, points with severe attacks exhibiting specific climatic conditions. In summary, this study provides crucial insights into OLB’s behaviour, emphasizing the role of climatic and environmental factors in its invasive tendencies.